Optimal design and analysis of a new thermally actuated microscanner of high precision - Gambin W. L. (International Journal for Simulation and Multidisciplinary Design Optimization, 2008)
A design of a precise, thermally actuated microscanner is proposed, and next, its thermal and mechanical behaviour is considered. The device consists of a micromirror and four thermo-bimorph cantilevers with electric resistors. After the forming process, the mirror assumes an out-of-plane rest position. The process is very simple and compatible with the IC fabrication technique. The mirror is capable of two-dimensional (2D) scans for optical raster imaging. The scanner works both in a non-resonance (for the frame scanning) and resonance mode (for the raster scanning). The high precision of scanning action is achieved due to a special position of the mirror rotation axes with respect to the cantilever beams. The above position assures, that the distance of the mirror centre from the light source is the same during the whole scanning process and the inertial moments of movable parts, as well as the influence of air damping, are minimized. To find the optical angle amplitudes of the mirror, deflections of the cantilevers caused by changes of temperature are determined. The analysis of dynamic temperature distribution enables to determine the thermal cut-off frequency, below which the amplitude of mirror deflections is frequency-independent. To find the resonance frequencies of the device, the dynamical analysis of the scanner is performed and free vibrations of the considered system are examined.